Energy modeling approach to the global energy-mineral nexus: Exploring metal requirements and the well-below 2 °C target with 100 percent renewable energy. (1st September 2018) - Tokimatsu, Koji; Höök, Mikael; McLellan, Benjamin; Wachtmeister, Henrik; Murakami, Shinsuke; Yasuoka, Rieko; Nishio, Masahiro
Highlights: Original "100% Renewable" scenario was added to "Coal & Nuclear, Gas & Renewable". Fully decarbonization in all sectors was essential to meet the well-below 2 °C target. Metal requirement was estimated with several uncertainties across the scenarios. Vanadium was identified as distinctly critical metal. Abstract: Detailed analysis of pathways to future sustainable energy systems is important in order to identify and overcome potential constraints and negative impacts and to increase the utility and speed of this transition. A key aspect of a shift to renewable energy technologies is their relatively higher metal intensities. In this study a bottom-up cost-minimizing energy model is used to calculate aggregate metal requirements in different energy technology including hydrogen and climate policy scenarios and under a range of assumptions reflecting uncertainty in future metal intensities, recycling rate and life time of energy technologies. Metal requirements are then compared to current production rates and resource estimates to identify potentially "critical" metals. Three technology pathways are investigated: 100 percent renewables, coal & nuclear and gas & renewables, each under the two different climate policies: net zero emissions satisfying the well-below 2 °C target and business as usual without carbon constraints, resulting together in six scenarios. The results suggest that the three different technology pathways lead to an almost identical degree of warming without any climate policy, while emissions peaks within a few decades with a 2 °C policy. The amount of metals required varies significantly in the different scenarios and under the various uncertainty assumptions. However, some can be deemed "critical" in all outcomes, including Vanadium. The originality of this study lies in the specific findings, and in the employment of an energy model for the energy-mineral nexus study, to provide better understanding for decision making and policy development.